Phylogenetic Bioprospection of Secondary Compounds for the Fragrance and Flavour Industry (2023)
For millions of years, animals and plants have depended on each other to survive. All species resort to plants for nutrition, clothing, medicine, or even when we want to have a sensory or emotional experience. Secondary compounds are the chemical compounds responsible for the smells and flavours found in plants. To date, the way we have looked for VOCs has either been through ethnobotany or sheer luck in a process called bioprospection. This investigation proposes optimising the process of bioprospection by focusing on phylogenetically related plants for similar compounds and smells. This study offers a first glance at phylogenetic bioprospection as a way to search for VOCs more efficiently. This preliminary exploration has lead us to believe more research should be carried out on this topic. Through this method, we successfully identified a list of VOCs that indicate promising uses in the Fragrance and Flavour industry.